Dinamika Kepemimpinan Pendidikan di Madrasah Ibtidaiyah Unggulan Darul Mujtaba (MINDA): Manajemen Pendidikan Islam Modern - Mubarak, Fadhil; Larasati, Oktafiani (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2023)
This research aims to find out how management leadership works in the school environment. The research locus in this research is the Darul Mujtaba Unggulan Ibtidaiyah Madrasah (MINDA). The method used is a qualitative approach with a case study design. Data collection techniques were carried out using interviews, observation and documentation. The data analysis technique uses the qualitative data analysis model from Miles and Huberman. The research results show that Darul Mujtaba is an Islamic boarding school located in Kendalpayak village, Pakisaji subdistrict, Malang, East Java. This school was founded in 2022 to provide its students with formal Islamic education. Students learn the Koran using the UMMI method. Teachers use open modules in preparing learning activities in class. Literacy programs are carried out every day. However, even though it has various advantages, every educational institution certainly has disadvantages. The lack of leadership at Darul Mujtaba Madrasah Ibtidaiyah includes the lack of books in the library, the lack of a special room for the principal, 20% of the teaching staff have not graduated from Bachelor's degree, and the learning tools and technology have not been implemented optimally. Apart from that, another characteristic of Madrasah Unggul Darul Mujtaba Ibtidaiyah is its unique vision and mission. To achieve this vision, Madrasah Darul Mujtaba Unggulan Ibtidaiyah has indicators for achieving this vision, including the realization of noble morals; the realization of skilled and professional educators and education personnel; creating intelligent graduates.